The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5530/pc.2016.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Phytochemical Analysis and Antibacterial Activity Evaluation of Indian Terminalia spp. Against the Pharyngitis Causing Pathogen Streptococcus pyogenes.

Abstract: Introduction: Streptococcus pyogenes is a gram-positive, pathogenic bacterium which causes a variety of diseases including streptococcal pharyngitis, impetigo and rheumatic heart disease, depending on which tissue it infects. Many Terminalia spp. have documented therapeutic properties as general antiseptics, inhibiting the growth of a wide variety of bacterial species. Methods: Solvent extracts were prepared using Indian Terminalia spp. with documented ethnobotanical usage to treat bacterial infections, or pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…A high antioxidant capacity has been postulated as being responsible for the medicinal properties of many plants. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In particular, antioxidants have been linked to antibacterial, antifungal and antiviral activities, as well as anticancer properties. 26-44 . However, other studies have indicated that antioxidants may protect cells from oxidative stress and thus protect against cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high antioxidant capacity has been postulated as being responsible for the medicinal properties of many plants. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In particular, antioxidants have been linked to antibacterial, antifungal and antiviral activities, as well as anticancer properties. 26-44 . However, other studies have indicated that antioxidants may protect cells from oxidative stress and thus protect against cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous and ethyl acetate extracts were also good bacterial growth inhibitors, with zones of inhibition of 8.3 ± 0.6 mm and 7.5 ± 0.5 mm respectively. S. pyogenes can cause a variety of diseases including streptococcal pharyngitis, impetigo and rheumatic heart disease, 42,43 depending on which tissue it infects. Thus, our results indicate the potential of the A. mollucanas nut extracts in preventing and treating rheumatic heart disease, as well as these other diseases, The antimicrobial efficacy was further quantified by determining the MIC values for each extract against the microbial species which were determined to be susceptible.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Phytochemical analysis of the extracts was achieved as previously described [20,21] and used to determine the presence of triterpenoids, saponins, cardiac glycosides, tannins, phytosteroids, phenolic compounds, flavonoids, anthraquinones, and alkaloids.…”
Section: Qualitative Phytochemical Studiesmentioning
confidence: 99%
“…Antibacterial activity screening of the S. australe and S. luehmannii extracts was assessed using a modified disc diffusion assay [32,33]. Briefly, 100 µL of each individual isolate was grown separately in 20 mL of the appropriate broth until an approximate count of 10 8 cells/mL was reached.…”
Section: Evaluation Of Antibacterial Activitymentioning
confidence: 99%